PS-C03-5: REAL-WORLD DATA OF BLOOD PRESSURE IN DIALYSIS PATIENTS WITH AND WITHOUT DIABETES IN JAPAN USING THE WEB-BASED DATABASE. (January 2023) - Sakuma, Hirofumi; Matsuki, Motoki; Hasebe, Naoyuki; Nakagawa, Naoki
Abstract : Objective: Diabetic nephropathy was the most common primary disease among patients undergoing dialysis, and the number is growing each year. Despite advancements in dialysis technique, cardiovascular complications and mortality in dialysis patients with diabetes remain higher than in those without diabetes. Furthermore, hypertension is commonly known to contribute to the development of cardiovascular complications in dialysis patients, and we aimed to compare the systolic blood pressure (SBP) in dialysis patients with and without diabetes using the Web-based Analysis of Dialysis Data Archives (WADDA) system database. Design and Methods: From 2014 to 2020, we enrolled dialysis patients who had their predialysis SBP measured using the WADDA system 2.1. We classified SBP and evaluated its trends over time by gender, age, and presence of diabetes using the Japanese Society of Hypertension guidelines 2019 (JSH2019). Furthermore, we looked at the relationship between SBP and cardiovascular death in patients with and without diabetes. Results: Dialysis patients with diabetes (n = 168, 227) had a mean age of 69.2 (11.7) years versus 69.4 (13.3) years, a mean predialysis history of 5.5 (5.3) years versus 9.4 (9.3 years), and a mean dialysis SBP of 156.6 (25.0) mmHg versus 147.9 (23.6) mmHg, respectively. Dialysis patients with diabetes had higher rates of cardiovascular complications than those without diabetes. From 2014 to 2020, the percentage and absolute values of hypertension were higher in dialysis patients with diabetes than across all age groups and in both men and women. Patients with cerebrovascular death had a higher rate of hypertension, but there was no difference in the rate of grade I and II hypertension between the two groups. Conclusion: We summarized the recent trends in SBP of Japanese dialysis patients with and without diabetes using the WADDA system. Dialysis patients with diabetes had higher SBP than those without diabetes in all age groups and in both men and women. As a result, optimal blood pressure management for dialysis patients with and without diabetes is important for the prevention of cerebrovascular death.